ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA SMP DALAM MENYELESAIKAN SOAL MATEMATIKA MELALUI PROBLEM BASED LEARNING - Muhamad Arief Rahman; Sri Sutarni (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The purpose of this study is to describe and determine the factors that affect students' higher order thinking skills (Higher Order Thinking Skills) in working on math problems with problem based learning patterns. This research is a qualitative descriptive study in which class VIII SMP Muhammadiyah 5 Surakarta is the source of the research and all the data is obtained through tests and interviews.The results of the analysis stated that the students' higher-order thinking skills in doing math problems for class VIII SMP Muhammadiyah 5 Surakarta were classified in the sufficient category with details: (1) 17.64% of them had high-order thinking skills which were classified as very good; 29.41% good; 41.17% is sufficient; and 11.76% categorized as less. (2) The percentage of students' ability to answer questions at the level of analyzing is 52.94%, the level of evaluating is 47.05%, and the level of creating is 23.52%.